Decision Characteristics and Strategic Decision Process for Strategic Decision Output: A Conceptual Model - Syahoera Shafie, Ardila; Nik Muhammad, Nik Maheran; Ridzwan, Rikinorhakis Ridzwan (Journal of Advanced Research in Business and Management Studies, 2020)
Making good decisions is an important action to each manager. This is because the decision will affect on their business performance. Although many studies involving many factors that influence decision-making, but it still has not been able to guide managers to make the right strategic decisions making. There is still a strong need to test the relationship between the strategic decision making process output with contextual factors such as internal, external organization characteristics and decision specific characteristics. Relevant study on moderating effect of strategic decision process that enhances the relationship between decision process characteristics and decision output is still scanty. Therefore, the aim of this study is to propose a model based on the effect and impact of contextual factors on the strategic decision making process and at the same time to test the extent to which the nature of decision-making process (a moderating effect) enhance the quality of the decision-making process output. The variables proposed are decision specific characteristic, organizational (internal characteristics), and environmental (external characteristics) effect on quality and satisfaction of the decision output while having strategic decision process (rationality or comprehensiveness, decentralization and politicization) as a moderating factor. Hence, the end of this study will highlighted the several outcomes, which are; (1) if the situations where they make strategic decisions are highly dynamic, (2) if the organization is large, and (3) if the decision exerts a high level of impact on different areas of the organization.